Dielectric and magnetic properties of ferrite/poly(vinylidene fluoride) nanocomposites - Martins, P. (2012)
Particulate composite films of poly(vinylidene fluoride) and CoFe2O4 and NiFe2O4 ferrites were prepared from solvent casting and melt processing. The well dispersed ferrite nanoparticles nucleate the piezoelectric -phase of the polymer, but the different ferrites nucleate the whole polymer crystalline phase at different filler concentrations. The macroscopic magnetic and dielectric response of the composites demonstrates a strong dependence on the volume fraction of ferrite nanoparticles, with both magnetization and dielectric constant increasing for increasing filler content. The β-relaxation in the composite samples is similar to the one observed for -PVDF obtained by stretching. A superparamagnetic behavior was observed for NiFe2O4/PVDF composites, whereas CoFe2O4/PVDF samples develop a hysteresis cycle with coercivity of 0.3 T.